Chemically Modified Kenaf Bast Fibres Reinforced Polyster Composites - Mustahil, Noorul Linda Suraya (2012)
Kenaf is locally planted and having great potential as reinforcement in polymer composite. However, the limitation occurs due to the hydrophilic nature of cell wall polymers. The main purpose of this research is to explore the potential of the chemical modification of kenaf bast fibre to be use in high performance composites. Kenaf bast fibre was used as reinforcement and unsaturated polyester as polymer matrix. The chemical modification of kenaf bast fibres was carried out by using propionic and succinic anhydride. Five retention times were set which were 30, 60, 120, 180 and 240 minutes at 100 °C. Chemical modification was confirmed by increase in WPG and also FT-IR.